Meningkatkan Aktivitas, Karakter Disiplin, Dan Hasil Belajar Menggunakan Model Prestasi Pada Peserta Didik Kelas Iv SDN Kelayan Selatan 9 - Nurhayda, Nurhayda; Jannah, Fathul; Agusta, Akhmad Riandy; Sari, Raihanah (CV. ITTC INDONESIA, 2024)
The issue with this discovery is the lack of engagement, lack of discipline, and subpar learning outcomes in PPKn education. Attempts to address these issues through the utilization of the PERSASI paradigm. The aim is to describe and analyze activity, character of discipline, and learning outcomes. The type of research used PTK. The subject of the discovery was grade IV students of SDN Kelayan Selatan 9 as many as 4 meetings. This research was conducted in 4 meetings. The research was carried out over the course of four meetings. The findings data were analyzed using descriptive analytic approaches, which involved presenting the data through tables, graphs, and interpretations using percentages. The findings indicated a progressive improvement in teacher engagement during each meeting, ultimately reaching the